Amplitude and timing of electromyographic activity during sprinting - Jonhagen, S.; Ericson, M. O.; Nemeth, G.; Eriksson, E. (Scandinavian Journal of Medicine & Science in Sports, 1996)
The aim of this study was to make descriptive analyses of the muscle activities in the lower extremity during maximal sprinting. Nine healthy sprinters were examined during maximal sprinting using telemetric electromyography (EMG). Seven muscles of the lower extremities were investigated: biceps femoris, medial hamstrings (semimembranosus and semitendinosus), rectus femoris, gluteus maximus, tibialis anterior, lateral gastrocnemius and medial gastrocnemius. The recorded EMG levels during running were expressed as percentage of maximum voluntary isometric contractions (%max EMG). For each muscle, the normalized EMG was plotted during the whole running stride cycle and is presented for each muscle. The reason for using this method is to show that it is possible to compare different muscle activities in a runner as well as to make comparisons between runners. Lateral and medial hamstrings and gluteus maximus showed similar activities with peak levels of EMG during foot-strike. Rectus femoris had a two-peak activity, with one peak at the middle of the stance phase and the other during the swing phase. The tibialis anterior also showed a two-peak activity, but with the peaks at the beginning of the swing phase and just before foot-strike. The highest activities of the medial and lateral gastrocnemius occurred just before toe-off. Scand J Med Sci Sports 1996 Feb;6(1):15-21